Hubungan Preeklampsia dengan Kejadian Bayi Berat Lahir Rendah (BBLR) - Desi Pramita Sari; Trisna Yuni Handayani; Ayu Rosanti (Jurnal Anestesi, 2023)
Preeclampsia is one of the causes of AKI and IMR. The causes of maternal death in Batam City are preeclampsia/eclampsia 35.7%, bleeding 14.3% and other causes 50%. Mothers with preeclampsia have a greater risk of giving birth to babies with LBW when compared to mothers with pregnancies without complications. The aim of this study was to determine the relationship between preeclampsia and the incidence of low birth weight babies (LBW). Quantitative research method with observational analytic design, cross-sectional research design. The sample in this study were 35 women giving birth with mild pre-eclampsia at the Embung Fatimah Hospital. Sampling technique with total samplingl. Data analysis using Chi Square. The results of this study showed that there was a significant relationship between preeclampsia and the incidence of low birth weight babies (LBW) at Embung Fatimah Hospital, Batam City (P value = 0.003 <0.05). the Oods Ratio value is 13,500 (2,256-80,792) which means that mothers with preeclampsia are 13 times more at risk of giving birth to babies with LBW babies than mothers who do not have preeclampsia. Pregnant women should carry out continuous antenatal visits from the beginning of pregnancy, so that risk factors can be detected early.